Tanymastigites lusitanica sp. nov. (Crustacea: Branchiopoda: Anostraca) from Portugal, first representative of the genus in Europe - Machado, Margarida; Sala, Jordi (Zootaxa, 2013)
Tanymastigites lusitanica sp. nov., a new species of fairy shrimp, is described from puddles in unpaved roads in the Alentejo region, Portugal. The males of Tanymastigites lusitanica sp. nov. are readily separated from the rest of the species of the genus by the morphology of antennae, antennal appendages and penes. T. lusitanica sp. nov. is closely related to T. perrieri but differs from it by the presence of a proximal ventrolateral short ridge in the distal segment of the antenna, and by the absence of a big thorn-like outgrowth in the distal lateral “lip” of the basal part of the penis. T. lusitanica sp. nov. presents a simple lateral branch in the antennal appendage of males, instead of the bifurcated lateral branch present in T. brteki, T. cyrenaica and T. mzabica. The finding of this new species represents the first citation of this genus in Europe. An identification key is provided to separate the males of the different species of the genus.